CAVATI - A Case Study of Muthuvar Youth Dormitory System - S. V. Sajith Kumar
CAVATI is the single-sex sleeping residence of unmarried males amongst Muthuvar. It equips the adolescent Muthuvar with certain kind of social experience acquired over many years of nightly attendance in the Ca _ vat[i that is entirely in the hands of the adolescent Muthuvar themselves, quite away from adult or parental authority. The institution achieves a level of harmonization that gives the Muthuvar settlements a focus and a degree of mutual participation that would other wise be lacking.